Impact of HPV sample self‐collection for underscreened women in the renewed Cervical Screening Program. Issue 5 (21st March 2016) - Smith, Megan; Lew, Jie Bin; Simms, Kate; Canfell, Karen
Abstract: Objectives: In 2017, the National Cervical Screening Program in Australia will transition to 5‐yearly primary HPV screening for all women, irrespective of human papillomavirus (HPV) vaccination status. As an adjunct to the mainstream program, HPV testing on self‐collected samples will be offered under practitioner supervision to all unscreened and underscreened women aged 30–74 years. We quantified how different screening decisions affect the future risk of cervical cancer. Design: Simulation of outcomes for 100 000 previously unscreened women, aged 30 years and eligible for self‐collection, using a well‐established model of HPV natural history and cervical screening. Main outcome measures: Cumulative cancer diagnoses and deaths averted (compared with remaining unscreened) to age 84, number needed to treat for pre‐cancer (NNT) to avert each cancer diagnosis. Results: One round of self‐collected HPV screening at age 30 years would avert 908 cancer diagnoses and 364 cancer deaths in the cohort by age 84 (NNT, 5.8). Benefits would still be achieved were self‐collected screening delayed to age 40 (922 fewer diagnoses; 426 fewer deaths; NNT, 3.7) or 50 (684 fewer diagnoses; 385 fewer deaths; NNT, 3.2). However, the benefits associated with joining the mainstream screening program would be substantially larger (2002, 1623 or 1091 fewer diagnoses and NNT of 4.9, 3.7 or 3.4 by joining at age 30, 40 or 50 years respectively). The relative benefits of joining the mainstream program were similar for cohorts who had been offered vaccination. Conclusions: Offering HPV self‐collection has the potential to considerably improve outcomes for unscreened and underscreened women. Nevertheless, these findings underscore the need for concerted strategies to encourage these women to join the mainstream HPV screening program.